Formulasi dan Karakterisasi Nanokristal Meloksikam Menggunakan Kombinasi Penstabil Polimer dan Surfaktan untuk Meningkatkan Kelarutan - Al-Hakim, Nur Achsan; Sutarna, Titta Hartyana; Ratih, Hestiary; Azzara, Karina Putriani (Jurnal Ilmiah Medicamento, 2026)
Background: Low solubility in water is a major obstacle for Meloxicam (MLX) and has implications for its limited bioavailability. Nanocrystallization techniques show potential for improving drug solubility, but nanoparticles tend to aggregate, suggesting the use of a combination of Hydroxypropyl Methylcellulose (HPMC) and Decyl Glucoside (DG) as stabilizers to overcome this problem.Objective: This study aims to develop and characterize meloxicam nanocrystals (MLX-NC) with a combination of HPMC and DG in an effort to improve solubility. MLX-NC was synthesized using ultrasonication and dried by lyophilization.Methods: The resulting formulation exhibited excellent physical stability over 28 days, as evidenced by consistent particle size (~11 nm) and polydispersity index (<0.3). Physical evaluation and characterization were performed, including particle size analysis (DLS), zeta potential, particle morphology (SEM), thermal analysis (DSC), X-ray diffraction (XRD), and saturated solubility testing.Results: The MLX-NC formulation showed a more than 200-fold increase in solubility compared to pure MLX, from 0.005 mg/mL to 1.064 mg/mL. XRD and DSC analyses confirmed that the nanocrystallization process converted the crystalline phase of MLX into an amorphous phase. These results indicate that induced amorphization can significantly improve solubility.Conclusion: The solubility of MLX can be significantly improved using ultrasonication combined with HPMC and DG. This approach has the potential to overcome the solubility limitations of BCS Class II drugs.